Linking workforce diversity and contextual performance: The mediating role of interpersonal conflict and moderating role of supportive leadership - Zahra Ishtiaq Paul; Kashif Rathore; Muhammad Adnan Sial (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Despite increased recognition, South Asian organizations' interest in workforce diversity and its role in enhancing performance in a public environment remains limited. Interpersonal conflict has been a dilemma in collectivist and high power distant culture due to differences among supervisor and subordinate opinions, attributable to workforce diversity. Present study is an attempt to understand the relationship between workforce diversity and contextual performance keeping in view the mediating role of interpersonal conflict and moderating role of supportive leadership. The model is studied on primary data of 440 civil servants drawn through proportionate stratified sampling technique. Exploratory and confirmatory factor analyses are performed before model testing to establish variable construct validity. For model and hypotheses testing, structural equation modeling by using AMOS, and hierarchical regression analysis, by using SPSS is performed. The findings show a partial mediation of interpersonal conflict between workforce diversity and contextual performance. Moreover, moderating role of supportive leadership for workforce diversity and contextual performance in presence of interpersonal conflict is also found. The index of moderated mediation also supported the presence of moderated mediation. The paper reaffirms the social identity theory literature from Pakistan within South Asian region.
Keywords: 330; workforce diversity; attitudes towards diversity; diversity perception; diversity climate; contextual performance; interpersonal conflict; supportive leadership; civil services; Pakistan